2020
DOI: 10.3390/ma13102231
|View full text |Cite
|
Sign up to set email alerts
|

Impedance-Based Monitoring of Mesenchymal Stromal Cell Three-Dimensional Proliferation Using Aerosol Jet Printed Sensors: A Tissue Engineering Application

Abstract: One of the main hurdles to improving scaffolds for regenerative medicine is the development of non-invasive methods to monitor cell proliferation within three-dimensional environments. Recently, an electrical impedance-based approach has been identified as promising for three-dimensional proliferation assays. A low-cost impedance-based solution, easily integrable with multi-well plates, is here presented. Sensors were developed using biocompatible carbon-based ink on foldable polyimide substrates by means of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 43 publications
0
22
0
Order By: Relevance
“…To overcome this major bundle and endow cells softer interfaces, significant effort has been directed towards using flexible low-cost substrates in the manufacturing of the sensing devices, which in turn, has deviated the fabrication methods from the standard clean-room facilities. A very recent example was reported by Tonello et al who used carbon-based monopolar electrodes patterned on flexible polyimide substrate to monitor (using impedance) mesenchymal stromal cells seeded into scaffolds of gelatin-chitosan [ 15 ]. Other studies have shown the potential of printed electronics for the development of sensors mechanically compliant to cells, able to monitor a variety of biomarkers and cell behaviors [ 16 , 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…To overcome this major bundle and endow cells softer interfaces, significant effort has been directed towards using flexible low-cost substrates in the manufacturing of the sensing devices, which in turn, has deviated the fabrication methods from the standard clean-room facilities. A very recent example was reported by Tonello et al who used carbon-based monopolar electrodes patterned on flexible polyimide substrate to monitor (using impedance) mesenchymal stromal cells seeded into scaffolds of gelatin-chitosan [ 15 ]. Other studies have shown the potential of printed electronics for the development of sensors mechanically compliant to cells, able to monitor a variety of biomarkers and cell behaviors [ 16 , 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, choosing and monitoring the temporal changes of the right controls is crucial when performing impedance measurements. Tonello et al used a different equation to calculate the CI, namely [ 32 ]. In this case they were looking at time point variations by subtracting the impedance of the cells at the different time points and comparing them to the gel in the absence of cells.…”
Section: Discussionmentioning
confidence: 99%
“…Note that it is also not clear whether Lee et al immersed the cell-free hydrogels in cell medium or protein-free PBS, in which case the changes could be more easily correlated to cell proliferation. More recently, Tonello et al measured the impedance of human mesenchymal stromal cells in gelatin-chitosan hybrid hydrogel scaffolds [ 32 ]. These cells did not form spheroids but rather individually proliferated within the hydrogel.…”
Section: Discussionmentioning
confidence: 99%
“…The opportunities of the printing approach for impedimetric biosensing mainly refer to the possibility to exploit novel nanostructured inks to enhance SNR and to the availability of biocompatible organic inks to improve the integration of sensing elements in biological environments. Thus, due to the limited invasiveness of the technique, printable organic and degradable inks can also be deposited on the electrode to investigate live cells, allowing impedimetric monitoring during a long-term culture both in 2D and 3D environments [80,81].…”
Section: Impedimetricmentioning
confidence: 99%